Mechanical Response and Shear-Induced Initiation Properties of PTFE/Al/MoO3 Reactive Composites - Junyi Huang (Materials, 2018)
Polytetrafluoroethylene/aluminum/molybdenum oxide (PTFE/Al/MoO3) reactive composites of a volume ratio of 60:16:24 were studied in this research. Quasi-static compression, dynamic compression and drop-weight experiments were performed to explore the mechanical response and the shear-induced initiation properties of the composites. Mesoscale images of the specimens after sintering demonstrate that PTFE, Al and MoO3 powders were evenly mixed and no chemical reaction occurred after the materials were stirred, pressed and sintered. The yield stress and compressive strength of PTFE/Al/MoO3 specimens are sensitive to strain rate within the range of 10−3~3 × 103 s−1, and the yield stress shows a bilinear dependence on the logarithm values of strain rate. The established Johnson-Cook constitutive model based on the experimental data can describe the mechanical response of PTFE/Al/MoO3 material well. Drop-weight tests show that the PTFE/Al/MoO3 specimens can react violently when impacted, with the characteristic drop height (H50) calculated as 51.57 cm. The recovered specimens show that the reaction started from the outer edge of the specimen with the largest shear force and the most concentrated shear deformation, indicating a shear-induced initiation mechanism. The reaction products of PTFE/Al/MoO3 specimens were AlF3, Al2O3, Mo and C, demonstrating that redox reaction occurred between PTFE and Al, and between Al and MoO3.